Substrate Stiffness Regulates Cholesterol Efflux in Smooth Muscle Cells - Mao, Xiuli; Tan, Yiling; Wang, Huali; Li, Song; Zhou, Yue (Frontiers in Cell and Developmental Biology, 2021)
The infiltration and deposition of cholesterol in the arterial wall play an important role in the initiation and development of atherosclerosis. Smooth muscle cells (SMCs) are the major cell type in the intima. Upon exposure to cholesterol, SMCs may undergo a phenotype switching into foam cells. Meanwhile, the pathological processes of the blood vessel such as cholesterol deposition and calcification induce the changes in the substrate stiffness around SMCs. However, whether substrate stiffness affects the cholesterol accumulation in SMCs and the formation of foam cells is not well-understood. In this study, SMCs were cultured on the substrates with different stiffnesses ranging from 1 to 100 kPa and treated with cholesterol. We found that cholesterol accumulation in SMCs was higher on 1 and 100 kPa substrates than that on intermediate stiffness at 40 kPa; consistently, total cholesterol (TC) content on 1 and 100 kPa substrates was also higher. As a result, the accumulation of cholesterol increased the expression of macrophage marker CD68 and downregulated SMC contractile marker smooth muscle α-actin (ACTA2). Furthermore, the mRNA and protein expression level of cholesterol efflux gene ATP-binding cassette transporter A1 (ABCA1) was much higher on 40 kPa substrate. With the treatment of a liver X receptor (LXR) agonist GW3965, the expression of ABCA1 increased and cholesterol loading decreased, showing an additive effect with substrate stiffness. In contrast, inhibition of LXR decreased ABCA1 gene expression and increased cholesterol accumulation in SMCs. Consistently, when ABCA1 gene was knockdown, the cholesterol accumulation was increased in SMCs on all substrates with different stiffness. These results revealed that substrate stiffness played an important role on SMCs cholesterol accumulation by regulating the ABCA1 expression. Our findings on the effects of substrate stiffness on cholesterol efflux unravel a new mechanism of biophysical regulation of cholesterol metabolism and SMC phenotype, and provide a rational basis for the development of novel therapies.